IDENTIFIKASI PERMASALAHAN DAN STRATEGI PENGELOLAAN TAMAN HUTAN RAYA NURAKSA - Syaputra, Maiser (Wanamukti: Jurnal Penelitian Kehutanan, 2019)
Tahura is a nature conservation area with a purpose to collecting natural or non-native plants and or animals, native and or non-native species, which are utilized for research, science, education, supporting cultivation, culture, tourism and recreation. As a conservation area whose territory is directly adjacent to the community, Nuraksa Forest Park is a source of economy and life for the surrounding community so that it can be said that there is community dependence on land in the area. This is a challenge in managing the area. In an effort to provide management direction so that the functions and benefits that have been regulated in the legislation and the achievement of the goals that have been formulated can be achieved, the perceived need for activities to identify problems and management strategies of Nuraksa Forest Park. The research was carried out through a series of activities, which consisted of literature studies, interviews and field surveys. The results of the SWOT analysis of the management of Nuraksa Forest Park are in quadrant III. This shows that Nuraksa Forest Park faces enormous opportunities, but on the other hand faces several internal obstacles / weaknesses. The strategy that must be implemented is to minimize the internal problems of the institution so that it can seize better opportunities.